READING MEDIATION ACTIVITIES IN CHEMISTRY CLASSES ON HEALTHY EATING AND THE PERIODIC TABLE - da Paixão Júnior, Hélio Nascimento; da Costa, Josineide Pantoja; Pessoa, Wilton Rabelo (Seven Editora, 2026)
The study of Chemistry can broaden the students' view of their universe of experiences, while considering such contexts can facilitate the understanding of this science. However, we realize that there is still resistance to its study by students, especially when faced with a teaching that privileges nomenclatures and calculations. Such teaching makes the student perceive chemistry from a stereotyped view, or in his words, as 'an even more complicated version of mathematics'. The present work proposes to present and discuss contributions of the interaction between reading mediation and chemistry teaching, since the use of scientific texts as a didactic resource can be considered as a means of facilitating. We start from the idea that, arousing curiosity in the search for new information, motivates the student to get involved in their learning, so it is important to promote their enculturation from elementary school, with the use of scientific language in the teaching and learning process of Chemistry. This research aims to propose reading mediation as a didactic resource in the teaching of Chemistry, through scientific literature, with the use of scientific articles - AC or scientific popularization texts - TDC, in order to promote and improve the construction of knowledge in the classroom. AC or TDC reading mediation are used as learning vehicles for students in the first year of high school, in a School of the Public Teaching Network of Ilha de Mosqueiro/PA and, above all, as a way to help students to think and to position itself critically before society. The preliminary results of this research suggest that reading mediation, associated with writing and discussion activities are relevant factors in the acquisition of chemical knowledge, contributing to the formation of a conscious and critical student about social problems. In summary, this interaction established between reader and scientific text can contribute to making learning more effective.